Executive function as a mechanism linking socioeconomic status to internalizing and externalizing psychopathology in children and adolescents. (June 2021) - McNeilly, Elizabeth A.; Peverill, Matthew; Jung, Jiwon; McLaughlin, Katie A.
Abstract: Introduction: The association between low socioeconomic status (SES) in childhood and increased risk for psychopathology is well established, but the mechanisms explaining this relationship are poorly understood. Here, we investigate the potential role of difficulties in executive functioning (EF) as a mechanism linking childhood and adolescent SES with externalizing and internalizing psychopathology. Methods: We examined whether difficulties with EF mediated the association between SES and externalizing and internalizing psychopathology in two cross-sectional samples of children and adolescents (Study 1: N = 94, ages 6–18, 51.1% male; Study 2: N = 259, ages 8–16, 54.1% male) from diverse SES backgrounds in the United States. EF was measured through behavioral tasks and parent-reported behavioral regulation (BR). Results: In both samples, children and adolescents from lower SES families were more likely to experience both externalizing and internalizing psychopathology than youth from more advantaged backgrounds and exhibited greater EF difficulties – they had lower performance on a task measuring inhibitory control and lower parent-rated BR. Reduced inhibitory control and BR, in turn, were associated with higher externalizing and internalizing psychopathology. In Study 1, difficulties with BR mediated the association of low-SES with both externalizing and internalizing psychopathology. In Study 2, low inhibitory control mediated the association between low-SES and externalizing psychopathology. These findings largely persisted after adjusting for exposure to violence, a form of adversity that is common in children from low-SES backgrounds. Conclusions: These findings suggest that reduced EF may be an underlying mechanism through which low-SES confers risk for psychopathology in children and adolescents.